Optimization of a laser plasma-based x-ray source according to WDM absorption spectroscopy requirements - A. S. Martynenko (Matter and Radiation at Extremes, 2021)
X-ray absorption spectroscopy is a well-accepted diagnostic for experimental studies of warm dense matter. It requires a short-lived X-ray source of sufficiently high emissivity and without characteristic lines in the spectral range of interest. In the present work, we discuss how to choose an optimum material and thickness to get a bright source in the wavelength range 2 Å–6 Å (∼2 keV to 6 keV) by considering relatively low-Z elements. We demonstrate that the highest emissivity of solid aluminum and silicon foil targets irradiated with a 1-ps high-contrast sub-kJ laser pulse is achieved when the target thickness is close to 10 µm. An outer plastic layer can increase the emissivity even further.